2022
DOI: 10.3389/fonc.2022.1014671
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Chronic neutrophilic leukemia associated with monoclonal gammopathies. A case series and review of genetic characteristics and practical management

Abstract: Chronic neutrophilic leukemia (CNL) is a rare but potentially aggressive BCR::ABL1 negative myeloproliferative neoplasm, characterized by sustained mature, neutrophilic leukocytosis. The discovery of key driver mutations in the colony-stimulating-factor-3 receptor (CSF3R) gene resulted in the updated World Health Organization (WHO) diagnostic criteria in 2016. A significant number of CNL cases have been associated with plasma cell dyscrasias, predominantly multiple myeloma (MM) and monoclonal gammopathy of unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Further, patients with MGUS with neutrophilia had significantly longer survival than those with isolated CNL. Vermeersch et al (4) found that median survival duration after diagnosis of CNL was 8 years, which may be attributable to some misdiagnoses of CNL; however, median survival of patients in our summary was 22 months, similar to the median survival duration of patients with isolated CNL.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Further, patients with MGUS with neutrophilia had significantly longer survival than those with isolated CNL. Vermeersch et al (4) found that median survival duration after diagnosis of CNL was 8 years, which may be attributable to some misdiagnoses of CNL; however, median survival of patients in our summary was 22 months, similar to the median survival duration of patients with isolated CNL.…”
Section: Discussionsupporting
confidence: 58%
“…As a rare subtype of MPN, CNL has been reported as associated with PCD in 16 cases to date. In addition, we also found two cases of CNL associated with lymphoma, namely follicular lymphoma and diffuse large B-cell lymphoma ( 4 , 7 ). This phenomenon suggests that CNL may be more inclined to associated with PCD instead of coexisting by chance.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Finally, this report describes a correlated response to BD between PB neutrophils, spleen size, monoclonal component, and serum G‐CSF level. [11, 12] These results suggest that PC‐targeted therapy is efficient in such case and may limit the risk of clonal evolution into a myeloid malignancy by decreasing G‐CSF production.…”
Section: Figurementioning
confidence: 95%
“…BM aspirate revealed a graft-donor myelodysplastic syndrome (MDS) with excess of blast (12%), male karyotype with monosomy 7 associated with TET2 Q1545* (VAF 46%) and ETV6 R418K (VAF 45%) Finally, this report describes a correlated response to BD between PB neutrophils, spleen size, monoclonal component, and serum G-CSF level. [11,12] These results suggest that PC-targeted therapy is efficient in such case and may limit the risk of clonal evolution into a myeloid malignancy by decreasing G-CSF production.…”
mentioning
confidence: 88%